Surface electromyography analysis of ankle flexor and extensor activity under different standing stability levels - Fangchao Wu; Jiahe Zhang; Kezhen Yang; Yangzhen Li; Zetong Li; Tian Li; Jianhua Li (Journal of Orthopaedic Surgery, 2024)
Background: To observe the activation strategies of the ankle muscles using surface electromyography (sEMG) during single-leg standing (SLS) and both-leg standing (BLS) on flat ground (FG), soft mat (SM), and BOSU ball (BB) surfaces. Methods: Thirty healthy young adults participated in the study. The muscle activities of the tibialis anterior (TA) and gastrocnemius medial (GM) were measured on the three surfaces during SLS and BLS. Electromyographic evaluations of the TA and GM were recorded during maximum voluntary isometric contractions (MVIC). Muscle activation was evaluated using MVIC%, and muscle co-contraction was evaluated using the co-contraction index (CI). Results: A statistically significant increase was observed in the MVIC% of the TA, GM, and CI on the three surfaces during SLS compared to BLS, except for the comparison of CI on BB between SLS and BLS (t = −1.35, p = 0.19). The MVIC% of the TA and GM during SLS and BLS on BB was significantly increased in comparison with FG and SM. The CI during BLS on BB increased compared to FG (t = 3.19, p < 0.01) and SM (t = 4.64, p < 0.01). The CI during BLS on SM (t = −1.46, p = 0.15) decreased when compared to FG but without statistical significance. Conclusions: SLS and unstable surfaces can induce greater muscle activation, and SLS can have a greater influence on ankle muscles.